With or Without U? Testing the Hypothesis of an Inverted U-Shaped Union Membership-Age Relationship - Claus Schnabel; Joachim Wagner (Contemporary Economics)
In this note, we apply a new test by Lind and Mehlum (2010), casting doubt on the claim proposed by Blanchflower (2007) that the probability of unionisation follows an inverted U-shaped pattern in age with a maximum in the mid- to late 40s. With this new test for an inverted U-shaped pattern, which has not been applied to the age-membership nexus before, and by constructing exact confidence intervals for the maximum value, we demonstrate that – at least with respect to West Germany – Blanchflower’s hypothesis does not hold. Our findings suggest that more definitive evidence is needed before the existence of international unionisation-age patterns can be taken for granted.